Coimmunoprecipitation of reversibly glycosylated polypeptide with sucrose synthase from developing castor oilseeds. Issue 23 (14th November 2017) - Fedosejevs, Eric T.; Liu, Leo N.C.; Abergel, Megan; She, Yi‐Min; Plaxton, William C.
Abstract : The sucrose synthase (SUS) interactome of developing castor oilseeds (COS; Ricinus communis ) was assessed using coimmunoprecipitation (co‐IP) with anti‐(COS RcSUS1)‐IgG followed by proteomic analysis. A 41‐kDa polypeptide (p41) that coimmunoprecipitated with RcSUS1 from COS extracts was identified as reversibly glycosylated polypeptide‐1 (RcRGP1) by LC‐MS/MS and anti‐RcRGP1 immunoblotting. Reciprocal Far‐western immunodot blotting corroborated the specific interaction between RcSUS1 and RcRGP1. Co‐IP using anti‐(COS RcSUS1)‐IgG and clarified extracts from other developing seeds as well as cluster (proteoid) roots of white lupin and Harsh Hakea consistently recovered 90 kDa SUS polypeptides along with p41/RGP as a SUS interactor. The results suggest that SUS interacts with RGP in diverse sink tissues to channel UDP‐glucose derived from imported sucrose into hemicellulose and/or glycoprotein/glycolipid biosynthesis. Abstract :